What is evolutionary about regional systems of innovation? Implications for regional policy - Elvira Uyarra (The University of Manchester, Manchester Business School, 2008)
The literature on Regional Systems of Innovation (RSI) has produced an extensive body of research in recent years and has been used widely as a framework for the design and implementation of policies in a variety of regional contexts. However, certain lack of clarity remains in relation to the defining elements and the dynamics of RSI. This lack of clarity is motivated by the fact that the concept of RSI is influenced by a number of theories and approaches, and in particular institutional, systemic and evolutionary approaches to innovation and learning. As a result of this mix of influences, the concept of RSI can result in different and even conflicting theoretical assumptions and policy rationales. To overcome these shortcomings it is necessary to revisit and adequately incorporate evolutionary ideas in regional systems of innovation.
Keywords: 330; regional systems of innovation; regional policy; innovation policy; evolutionary economics; institutions; Innovationspolitik; Regionalpolitik; Evolutionsökonomik; Neue Institutionenökonomik